Disorganization and Financial Collapse - Dalia Marin; Monika Schnitzer (Center for Economic Studies and ifo Institute (CESifo), 2000)
Recently, Blanchard and Kremer (BK) argued that disorganization has led to the output decline in the former Soviet Union. In this paper we introduce liquidity and credit constraints into the BK model and show how these problems can alleviate the hold-up problem. We argue further that barter creates a hostage which allows to deal with disorganization when credit enforcement is prohibitively costly. The theory helps to explain how the three observed phenomena of output decline, inter-firms arrears and barter in transition economies are connected. Based on a survey of 165 barter deals in the Ukraine in 1997, we reproduce the BK result with firm level and deal specific data and we show that in addition to the input shortage the financial shortage and barter have each an important effect on output growth.
Keywords: 330; Transition; financial crisis; output fall; credit constraint; barter; hold-up